Prediction of Visual Behaviour in Immersive Contents - Nuno Rodrigues de Castro Santos Silva (2022)
In the world of broadcasting and streaming, multi-view video provides the ability to present multiple perspectives of the same video sequence, therefore providing to the viewer a sense of immersion in the real-world scene. It can be compared to VR and 360° video, still, there are significant differences, notably in the way that images are acquired: instead of placing the user at the center, presenting the scene around the user in a 360° circle, it uses multiple cameras placed in a 360° circle around the real-world scene of interest, capturing all of the possible perspectives of that scene. Additionally, in relation to VR, it uses natural video sequences and displays. One issue which plagues content streaming of all kinds is the bandwidth requirement which, particularly on VR and multi-view applications, translates into an increase of the required data transmission rate. A possible solution to lower the required bandwidth, would be to limit the number of views to be streamed fully, focusing on those surrounding the area at which the user is keeping his sight. This is proposed by SmoothMV, a multi-view system that uses a non-intrusive head tracking approach to enhance navigation and Quality of Experience (QoE) of the viewer. This system relies on a novel "Hot&Cold" matrix concept to translate head positioning data into viewing angle selections. The main goal of this dissertation focus on the transformation and storage of the data acquired using SmoothMV into datasets. These will be used as training data for a proposed Neural Network, fully integrated within SmoothMV, with the purpose of predicting the interest points on the screen of the users during the playback of multi-view content. The goal behind this effort is to predict possible viewing interests from the user in the near future and optimize bandwidth usage through buffering of adjacent views which could possibly be requested by the user. After concluding the development of this dataset, work in this dissertation will focus on the formulation of a solution to present generated heatmaps of the most viewed areas per video, previously captured using SmoothMV.